تقويم جودة الامتحان الالكتروني لرخصة مزاولة مهنة التدريس - عبدالله,عمر; بلة,الصديق (University of Eloued جامعة الوادي, 2024)
ملخص: هدفت الدّراسة إلى تقويم جودة الامتحان الالكتروني لرخصة مزاولة مهنة التدريس الذي أقامه مجلس المهن التربوية والتعليمية بمحلية شرق الجزيرة بالسودان في نوفمبر2022م، تم إجراء الدّراسة في كلية التربية جامعة البُطانة العام الدّراسي (2022-2023م)، ولتحقيق أهداف الدّراسة تم استخدام المنهج الوصفيّ التّحليليّ، من خلال أداة الاستبانة، وتكونت عينة الدّراسة من عدد (131) من الجالسين لامتحان مزاولة مهنة التدريس، وهم يشكلون نسبة حوالي (11%) من مجتمع الدّراسة، تم اختيارهم بالطّريقة العشوائيّة البسيطة، ولمعالجة البيانات إحصائياً تم استخدام برنامج الحزم الإحصائّية للعّلوم الاجتماعيّة (SPSS)، أهم نتائج الدراسة: التجهيزات للامتحان الالكتروني لرخصة مزاولة مهنة التدريس تحققت بدرجة عالية بوسط حسابي بلغ(2.76%).تحققت مميزات الامتحان الالكتروني لرخصة مزاولة مهنة التدريس بدرجة عالية. بوسط حسابي بلغ (2.49%). توجد فروق ذات دلالة إحصائية في متوسط تقديرات المفحوصين حول جودة الامتحان الالكتروني لرخصة مزاولة مهنة التدريس لصالح الإناث. وأوصت الدراسة بـ: مراعاة شمولية الامتحان لكل جوانب التعلم (التربوية والمادة المتخصصة)، ضرورة اختيار التوقيت المناسب لعقد الامتحان. Abstract The study aimed to evaluate the quality of the electronic exam for the teaching profession license conducted by the Council of Educational and Teaching Professions in East Gezira locality, Sudan, in November 2022. The study was conducted at the Faculty of Education, University of Al-Butana, during the academic year (2022-2023). To achieve the study's objectives, the descriptive-analytical method was used through a questionnaire as the study tool. The study sample consisted of 131 individuals who sat for the teaching profession license exam, representing approximately 11% of the study population. They were selected using the simple random sampling method. For statistical data processing, the Statistical Package for the Social Sciences (SPSS) was used. Key Findings of the StudyThe preparations for the electronic exam for the teaching profession license were highly achieved with a mean score of 2.76. The advantages of the electronic exam for the teaching profession license were highly achieved with a mean score of 2.49. There are statistically significant differences in the average ratings of the examinees regarding the quality of the electronic exam for the teaching profession license in favor of females. The Study Recommended: Considering the comprehensiveness of the exam for all aspects of learning (educational and specialized subjects). Ensuring the appropriate timing for holding the exam
من وجهة نظر الجالسين للامتحان المقام بكلية التربية بجامعة البطانة، السودان، 2022م
Keywords: التّعليم الالكتروني; الاختبار الالكتروني; التمهين; الجودة; التّعليم العام; E-learning; electronic testing; professionalization; quality; general education